Aktivitas antioksidan ekstrak dan fraksi cangkang biji sacha inchi (Plukenetia volubilis L.) terhadap DPPH (1,1-Difenil-2-Pikrilhidrazil) - Novia Yanti, Masyitah; Chintara Wanda, Aulia; Sartika, Lili; Iswandi, Iswandi (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2024)
Free radicals such as cigarette smoke, ultraviolet radiation, radical triggers in food and pollution. To prevent these free radicals, antioxidants are needed. One of the plants that has antioxidant activity is Sacha Inchii seeds. Sacha inchi seeds contain polyunsaturated fatty acids such as omega-3 (α - linolenic acid), omega-6 (linoleic acid), monounsaturated fatty acids such as omega-9 (oleic acid), vitamin E (α-tocopherol and δ tocopherol), vitamin A (carotenoids), flavonoids, tannins, phenolic compounds and β-sitosterol. The purpose of this study was to determine the antioxidant activity of the extract and fraction of sacha inchi seed shells against DPPH radicals (1,1-diphenyl-2-picrylhydrazyl) with IC50 parameters and to determine the group of compounds that play a role in the antioxidant activity test. Sacha inchi seed shells were extracted by maceration method using 96% ethanol. The extract obtained was then suspended with water and then fractionated with n-hexane and ethyl acetate. The extract of sacha inchi seed shells and the fractions obtained were then tested for their antioxidant activity against DPPH radicals. The test was carried out in 5 concentration series by adding 4.0 ml of the test solution with 1.0 ml of 0.45 mM DPPH. Activity against free radicals was measured using a spectrophotometer at a wavelength of 517 nm and the IC50 value was determined using probit analysis. The positive control used was Rutin. Identification of compound groups can be done using the Thin Layer Chromatography (TLC) method, the results of which can be identified with a spray reagent or compared with a standard standard. The results showed that the sacha inchi seed shell has antioxidant activity with IC50 values ​​of ethanol extract, n-hexane fraction, ethyl acetate fraction, water fraction respectively having antioxidant activity with IC50 values ​​of 25.3 µg/ml, 52.63 µg/ml, 21.42 µg/ml, and 39.5 µg/ml. The ethyl acetate fraction has the strongest activity compared to the others with an IC50 value close to the Routine IC50 of 21.42 µg/ml as a positive control. The sacha inchi seed shell has compounds that have the potential as antioxidants, namely the flavonoid, saponin, tannin and triterpenoid compounds.